(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper studies the wormhole attack in the mobile adhoc network. This paper modifies the AODV routing protocol to detect and recover from the wormhole routing attack. The result analysis of modified AODV is done by varying the number of wormhole nodes. The result analysis is done by using the PDR and the end 2 end delay. The simulation results confirm the better performance of the modified AODV.